Microorganismos eficientes activados en el desarrollo vegetativo de Moringa oleífera. Loreto, Perú - Cardenas Torres, Dayana Michelle (2025)
The production of quality green biomass for livestock feed is a priority for the faculty of agronomy, as is the case of the present research work entitled EFFICIENT MICROORGANISMS ACTIVATED IN THE VEGETATIVE DEVELOPMENT OF Moringa oleífera. LORETO, PERU. Work carried out in the humid tropics in the community of Zungarococha. With a completely randomized block design, with 16 experimental units. Arriving at the following results in the use of effective microorganisms in the forage of Moringa oleífera. MORINGA. That for the indicators of plant height and percentage of coverage, the T3 treatment (75 ml activated EM 1/liter of water), surpassed the other treatments with the following results of 1.65 meters in height and 81.5 percent coverage. Regarding yield, treatment T3 (75 ml activated EM-1/liter of water) and treatment T2 (50 ml activated EM-1/liter of water) did not show statistically significant differences, with values of 13,600 and 12,700 kilos per hectare under humid tropical conditions.